Simulation of coarse mixing of the vapour explosion - Ohashi, Hirotada; Takano, Takuya; Yang, Yanhua; Akiyama, Mamoru; Morii, Tadashi; Ogawa, Yumi (Computer Assisted Methods in Engineering and Science; Vol 2 No 2 (1995), 2023)
The vapour explosion is a violent explosive phenomenon which may occur when two kinds of liquid of different temperature contact suddenly. Analysis of this phenomenon is needed in terms of safety evaluation of nuclear reactors, examination of volcanic eruptions and assurance of safety of various industrial processes. We have developed a simulation method applicable to coarse mixing of the vapour explosion. This process, including complex thermo-hydrodynamics, requires handling of multi-phase and multi-component. We employed CHAMPAGNE which is a general-purpose multi-phase flow code and modified it make it suitable for the analysis of the vapour explosion . Specifically, we improved interfacial heat transfer models and incorporated compensation for numerical dilution of the dispersed liquid . After some model calculations we simulated the MIXA experiment done at Winfrith. Details of the code modification and the simulation results are presented in this paper.